Stan łańcuchów dostaw na przykładzie firmy branży mięsnej - Cywińska, Beata (Current State of Supply Chain on the Example of Meat Processing Plant, 2005)
The paper contains an example of a tinned meat producer who is not convinced whether it is worth undertaking activities in the area of supply chain networks. At present, due to the pressure of the market, the company carries out a strategy of low costs of production and aims at differentiating the product characteristics and ways of selling products.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1070, t. 1, s. 109-113